2014
DOI: 10.1136/thoraxjnl-2014-205278
|View full text |Cite
|
Sign up to set email alerts
|

A UK-based resource to support the monitoring and safe use of anti-TB drugs and second-line treatment of multidrug-resistant TB

Abstract: Using the best available evidence and expert consensus, this document provides guidance for adverse effect monitoring in multidrug-resistant TB (MDR-TB). It includes recommendations for baseline tests, routine drug and toxicity monitoring guides as well as individual drug monographs for all drugs currently available in the UK to treat TB. These recommendations provide a structure through which healthcare professionals can better manage the complex drug regimens required for the treatment of MDR-TB; minimising … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 3 publications
0
4
0
2
Order By: Relevance
“…Factorii de risc în dezvoltarea cardiotoxicității cu prelungirea intervalului QTc includ vârstnicii, sexul feminin, afecțiunile cardiace, inclusiv congenitale și dobândite, dezechilibru electrolitic și utilizarea concomitentă a altor medicamente cu potențial cardiotoxic. Pentru Bedaquilin rezultatele căutării sistematice au demonstrat o tolerabilitate bună, cu întreruperea administrării din cauza reacțiilor adverse în 3,4% și din cauza prelungirii intervalului QTc în 0,6% [18].…”
Section: Reacții Adverse Medicamentoase Imunologice șI Hematologiceunclassified
See 1 more Smart Citation
“…Factorii de risc în dezvoltarea cardiotoxicității cu prelungirea intervalului QTc includ vârstnicii, sexul feminin, afecțiunile cardiace, inclusiv congenitale și dobândite, dezechilibru electrolitic și utilizarea concomitentă a altor medicamente cu potențial cardiotoxic. Pentru Bedaquilin rezultatele căutării sistematice au demonstrat o tolerabilitate bună, cu întreruperea administrării din cauza reacțiilor adverse în 3,4% și din cauza prelungirii intervalului QTc în 0,6% [18].…”
Section: Reacții Adverse Medicamentoase Imunologice șI Hematologiceunclassified
“…Administrarea de H poate cauza producerea anticorpilor și apariția lupusului eritematos la 1% de pacienți, de asemenea,se poate agrava lupusul eritematos preexistent. Erupțiile cutanate au fost, de asemenea, raportate și pentru medicamentele antituberculoase de linia a doua, inclusiv și cele mai noi, precum Bedaquilin (Bdq) și Delamanid (Dlm) [10,18,28,29].…”
Section: Reacții Adverse Medicamentoase Imunologice șI Hematologiceunclassified
“…To enable an assessment of whether exposure to the external or, if available, internal exposure in the infant would raise health concerns, we consulted official sources such as approved material by a regulatory body (i.e., the official summary of product characteristics; SPC) and published material by a UK-based learned society produced by Potter et al [21], updated in 2021. The adverse effects enumerated there were assessed for whether they would be dose-dependent and whether a cut-off dose is known.…”
Section: Reid =mentioning
confidence: 99%
“…In patients treated with streptomycin, monitoring of the renal function as well as the auditory and vestibular function is essential [21] as these adverse effects are not uncommon and serious.…”
Section: Adverse Effectsmentioning
confidence: 99%
“…Due to the complexity of treatment regimens used for MDR-TB, national monitoring guidelines have been developed to aid monitoring for adverse effects during treatment. 1 A previous study identified that prior to the development of these monitoring guidelines the incidence of adverse effects associated with MDR TB medicines was high. 2 Objective To establish whether national guidelines for the monitoring of MDR-TB medicines at a tertiary centre are being adhered to.…”
mentioning
confidence: 99%